Manajemen Pelayanan Administrasi Kependudukan di Kantor Kecamatan Basidondo Kabupaten Tolitoli - Masrin Gafar (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to determine the Management of Population Administration Services at the Basidondo District Office, Tolitoli Regency. This type of research is a descriptive method with a qualitative approach. Data collection techniques used by Observation, Interview, Documentation. The informants in this study were 1 person from the Basidondo Subdistrict as key informants, 3 people from the District Administration and 3 people from the Basidondo Subdistrict community as supporting informants. The data analysis technique used is qualitative inductive in nature. From the results of this study it can be concluded that the implementation of Population Administration Service Management at the Basidondo District Office, Tolitoli Regency has not been carried out optimally because the three theoretical indicators used by the author are only two fulfilled, namely service culture and service system, but one indicator is not fulfilled, namely human Resources.